The Influence of Work Discipline And Communication on Employee Performance at PT Savana Rattan Furniture - Honesty Arief Sonjaya; Lissa Harry Sulistyowati; Sandi Nasrudin Wibowo (Rescollacom (Research Collaborations Community), 2026)
The purpose of this study is to examine how work discipline and communication partially (t) or simultaneously (f) affect the performance of PT Savana Rattan Furniture employees. PT Savana Rattan Furniture employees are the subjects and population in this study. In this study, the sampling technique used was saturated sampling, which included all 100 employees. The method used to collect data for this study was a questionnaire, while the analysis technique used in this study was multiple linear regression analysis. The results of this study indicate that work discipline has a significant positive effect on employee performance, as seen from the t-count being greater than the t-table 5.388>1.984, while organizational culture has a positive but insignificant effect, as seen from the t-count greater than the t-table 0.726<1.984. Simultaneously, the effect of the variables of work discipline and communication on employee performance is shown by F-count>F-table, namely 15.206 > 3.09. Partially, work discipline has a significance value of 0.000>0.05, communication has a significance value of 0.470>0.05, and simultaneously, work discipline and communication have a significance value of 0.000.